Peran Media Sosial di Internet pada Penerapan Proses Knowledge Management - Kurniali, Sartika (ComTech: Computer, Mathematics and Engineering Applications, 2011)
Knowledge management application on the internet keeps growing. It happens because the Internet offers new opportunities to use the knowledge assets, defines and spreads type of new knowledge assets, even to outside the organization. On the internet, appear social media that enable internet-based knowledge sharing system. As we know social media is not something new and has undergone many changes that allow for more interactive interaction and much greater number of users now. The research results showes that knowledge management and social media have nearly similar components. This allows the role of social media on the knowledge management application, such as collaboration tools coming with a clear business purpose.